Концептуальні засади протидії політичній злочинності [закінчення] - Орлов, Ю. В.; Orlov, Y. V.; Орлов Юрій Володимирович (Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 196-209., 2015)
Стаття присвячена описанню та поясненню системи основних заходів протидії політичній злочинності й чинників їх реалізації. Серед них виділено та охарактеризовано такі: формування безконфліктної прогресивної ідеології суспільного розвитку, а також економічні, інформаційні, правові, політичні заходи. Дається визначення поняття та характеристика підстав і умов застосування політико-кримінологічної технології масового спротиву як заходу протидії політичній злочинності.

Analysis of the most common paths of social development that emerged at the beginning of ХХІ century gives reasons to insist on increasing criminogenic potential of social contradictions, because of rejection from the principles of socialized liberalism, the intensification of social stratification according to ownership feature and many other factors. Interaction of the latter led to a systemic crisis of social management that embodied in the intensification of conflict zones of geopolitical interactions. The establishment of Ukraine as an arena of confrontation of competing geopolitical interests, the risk of turning it into a “gray zone” contains serious criminogenic threats, where political crime within their structure takes decisive instrumental position. In such circumstances of forming effective mechanisms of counteracting its manifestations is of a particular relevance.A lot of scholars paid attention to theoretical research of the issues of combating political crime. However, existing developments are largely fragmented, covering only certain measures of combating political crime, which necessitates the formation of a holistic, systemic vision of obstruction of its determination complex. The objective of the article is to describe and explain the conceptual principles of counteracting political crime. Sit is grounded that counteraction to its reproduction must come out from the destruction of its factors, to take into account the systemic links between them, as well as with external factors of geopolitical format. The following main groups of related activities aimed at reducing social danger of political crime are suggested: 1) measures of forming conflict-free progressive ideology of social development; 2) economic measures: conceptual reform of economic system based on the ideology of social liberalism; formation of the system of energy security of Ukraine on the basis of energy supplies of different sources, etc; 3) information security measures; 4) legal measures; 5) political measures. Special attention is paid to the scientific development of bases, forms and limits of applying political and criminological technology of mass resistance. It is offered to be understood as methodologically balanced complex of exceptional measures based on purposeful and generally managed lawful actions of majority of people that is aimed to persuade the state’s leaders to accept/reject a particular political solution, which is supported by the overwhelming majority of the population and is based on the absolute necessity of stopping criminal activity of political elites. Attention is focused on the delimitation of the coup d’etat as a political crime from the coup d’etat as an act of stopping political crime activity, elimination of criminalized political elites from the state leadership according to the following criteria: 1) presence of real, extreme social demand in the immediate elimination of the state leaders from their positions in the highest government bodies; 2) compliance of the taken decision to use political and criminological technology of mass resistance to the requirements of legality and national security. Perspective direction for further research remains theoretical development and specification of some groups of measures of counteracting political crime.

Статья посвящена описанию и объяснению системы основных мер противодействия политической преступности и факторов их реализации. Среди них выделены и охарактеризованы следующие: формирование бесконфликтной прогрессивной идеологии общественного развития, а также экономические, информационные, правовые, политические мероприятия. Даётся понятие и характеристика оснований, условий применения политико-криминологической технологии массового сопротивления в качестве меры противодействия политической преступности.
Закінчення. Початок див. Вісник кримінологічної асоціації україни, 2015, № 1 (9)
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; політична злочинність; протидія злочинності; ідеологія; соціальний лібералізм; інформаційна безпека; політична відповідальність; національна безпека; political crime; counteraction; ideology; social liberalism; information security; political responsibility; national security; политическая преступность; противодействие преступности; идеология; социальный либерализм; информационная безопасность; политическая ответственность; национальная безопасность; combating crime